Breathable fusible interlining cloth for coated fabrics and preparation method thereof

By synthesizing modified crosslinking agents and preparing polyurethane hot melt adhesive, the problem of poor bonding effect of existing bonding lining cloth after high temperature and water treatment is solved, and a high-performance breathable bonding lining cloth is realized, with good heat resistance and Water resistance.

CN116676791BActive Publication Date: 2025-02-11SHANGHAI TIANQIANG TEXTILE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310656139.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-05
Publication Date
2025-02-11
Estimated Expiration
2043-06-05
Patent Text Reader

Abstract

The present invention relates to the field of adhesive interlinings, and specifically to a breathable adhesive interlining for coated fabrics and a preparation method thereof. The present invention comprises mixing citric acid, polyethylene glycol and aminopropyl triethoxysilane to prepare a modified crosslinking agent; firstly subjecting citric acid to an esterification reaction with polyethylene glycol, and controlling the amount of reactants so that the polyethylene glycol reacts fully; then adding anhydrous ethanol and thionyl chloride to further react with unreacted carboxyl groups on the citric acid, and finally using aminopropyl triethoxysilane for grafting to introduce silicon oxygen bonds into the modified crosslinking agent; mixing the modified crosslinking agent with polyurethane to prepare a hot melt adhesive, coating the hot melt adhesive on the surface of the base fabric, and then melting, processing and finishing to obtain a heat-resistant and water-resistant breathable adhesive interlining.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesive interlining cloth, in particular to a breathable adhesive interlining cloth for coated fabrics and a preparation method thereof. Background Art

[0002] Coated fabric is a kind of fabric treated by special process. Solvent is used to dissolve the coating glue into a drooling state, and it is evenly coated on the surface of cotton, polyester, nylon and other fabrics through a round net, scraper or roller. After baking, the glue is fixed and covered on the surface of the fabric. Coated fabric is often used in defense, navigation, fishing, offshore oil wells, transportation, clothing and other fields. It is a common waterproof and breathable fabric.

[0003] Fusible interlining, also known as hot melt interlining, is an adhesive clothing accessory formed by coating hot melt adhesive on a woven, knitted or non-woven base fabric through coating technology equipment. Under a certain temperature and pressure, the adhesive melts and the interlining and the fabric are firmly attached together, thereby simplifying the processing technology to the greatest extent. In the field of clothing, with the continuous improvement of the quality of life, people's requirements for the performance of clothing are getting higher and higher. Combining fusible interlining with coated fabrics can prepare clothing with different functions such as waterproof, windproof, and breathable. Therefore, higher requirements are placed on the performance of fusible interlining. Summary of the invention

[0004] The object of the present invention is to provide a breathable adhesive interlining for coated fabrics and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] Step 1: adding citric acid, polyethylene glycol and p-toluenesulfonic acid to toluene, reflux reaction, and distillation under reduced pressure; adding anhydrous ethanol and thionyl chloride, reflux reaction, adding aminopropyltriethoxysilane after dehydration, reflux reaction, cooling, washing and drying to obtain a modified crosslinking agent;

[0007] Step 2: Mix polyethylene glycol, 1,4-butanediol, a modified crosslinking agent and an antioxidant, heat and stir to mix evenly, vacuum dry and dehydrate, cool and add isophorone diisocyanate and stannous octoate, discharge the material after reaction, seal and package, and place in an oven for aging to obtain a polyurethane hot melt adhesive;

[0008] Step 3: Take the base fabric and scour it; after washing with clean water, take out the base fabric; after pre-forming treatment, melt the polyurethane hot melt adhesive and apply it on the surface of the base fabric to obtain a breathable adhesive lining fabric for the coated fabric.

[0009] Furthermore, in step 1, the preparation method of the modified cross-linking agent is: add citric acid, polyethylene glycol, and p-toluenesulfonic acid to toluene, heat to 130-140°C, reflux, react for 20-26 hours, and distill under reduced pressure; add anhydrous ethanol and thionyl chloride, reflux at 70-80°C, react for 10-15 hours, after dehydration, add aminopropyltriethoxysilane, reflux at 90-100°C, react for 6-8 hours, cool, wash, and dry to obtain the modified cross-linking agent.

[0010] Furthermore, in step 1, the amounts of the components, by mole fraction, are 1 part of citric acid, 1 to 2 parts of polyethylene glycol, 0.005 to 0.05 parts of p-toluenesulfonic acid, 2 parts of toluene, 3 to 3.5 parts of anhydrous ethanol, 2.4 to 3 parts of thionyl chloride, and 2 to 2.2 parts of aminopropyltriethoxysilane.

[0011] Furthermore, in step 2, the preparation method of the polyurethane hot melt adhesive is specifically as follows: polyethylene glycol, 1,4-butanediol, a modified crosslinking agent and an antioxidant are mixed, heated at 110-140°C and stirred to mix evenly, vacuum dried and dehydrated for 2.5 hours, cooled to 65-75°C, isophorone diisocyanate and stannous octoate are added, the reaction is carried out for 20-30 minutes, the material is discharged, sealed and packaged, and placed in an oven at 70-90°C for aging for 6-8 hours.

[0012] Furthermore, in step 2, the amounts of the components used are, by weight, 70 to 85 parts of polyethylene glycol, 2 to 4 parts of 1,4-butanediol, 1 to 2 parts of a modified crosslinking agent, 0.1 to 0.2 parts of an antioxidant, 25 to 35 parts of isophorone diisocyanate, and 0.05 to 0.1 parts of stannous octoate.

[0013] Furthermore, in step 3, the refining temperature is 80-100° C., the bath ratio is 25-30:1, and the time is 30-60 min.

[0014] Furthermore, in step 3, the melting temperature of the polyurethane hot melt adhesive is 150-190°C.

[0015] Further, in step 3, the pre-setting treatment method is that the base fabric passes through 9 setting chambers in sequence, and the temperatures of each setting chamber are: 100-120°C in chamber 1, 100-120°C in chamber 2, 120-150°C in chamber 3, 120-150°C in chamber 4, 140-170°C in chamber 5, 140-170°C in chamber 6, 140-170°C in chamber 7, 140-170°C in chamber 8, 140-170°C in chamber 9, the vehicle speed is 30-40m / min, and the door width is 120-125cm.

[0016] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention first synthesizes a modified cross-linking agent, mixes it with polyethylene glycol, 1,4-butanediol, an antioxidant and isophorone diisocyanate to prepare a polyurethane hot melt adhesive; after the polyurethane hot melt adhesive is heated and melted, it is coated on a base fabric to obtain a heat-resistant and water-resistant breathable adhesive lining fabric. Among them, the modified cross-linking agent is formed by the reaction of citric acid, polyethylene glycol and aminopropyl triethoxysilane; the citric acid molecule contains 3 carboxyl groups and 1 hydroxyl group, and the carboxyl group can undergo esterification reaction with the alcohol hydroxyl group, so polyethylene glycol is first used to react with part of the carboxyl groups of citric acid to obtain an intermediate product with multiple functional hydroxyl groups, and the hydroxyl group can react with the isocyanate group in the polyurethane and be added to the polyurethane in the form of a cross-linking agent, thereby changing the original linear structure of the polyurethane, forming a three-dimensional cross-linked network structure, and improving the mechanical properties of the hot melt adhesive; in addition, after aminopropyl triethoxysilane is grafted with the intermediate product, a silicon-oxygen bond is introduced into the polyurethane, thereby improving the heat resistance of the polyurethane hot melt adhesive, which is beneficial to the thermal processing and heat treatment of the fabric.

[0017] In the present invention, the grafting of polyethylene glycol and aminopropyl triethoxysilane both needs to react with the carboxyl groups on citric acid through the alcohol hydroxyl groups, so the amount of reactants and the reaction order need to be limited. Through experiments, it is found that the reaction activity of polyethylene glycol and citric acid is higher and the reaction is controllable. Therefore, by adjusting the molar ratio of the reactants polyethylene glycol and citric acid (1-2): 1, the polyethylene glycol can be fully reacted while the citric acid can still leave excess unreacted carboxyl groups for aminopropyl triethoxysilane grafting. It should be noted that the reaction order of polyethylene glycol and aminopropyl triethoxysilane cannot be changed. When aminopropyl triethoxysilane is grafted, it needs to react in an ethanol environment, that is, ethanol is excessive. If aminopropyl triethoxysilane is grafted with citric acid first, the three carboxyl groups of citric acid will be completely reacted, so that it cannot react with polyethylene glycol, and the obtained polyurethane hot melt adhesive does not have a three-dimensional network structure and the bonding effect is poor. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] The materials used in the present invention and their sources are as follows: polyethylene glycol comes from Yisheng Biotechnology, model PEG-2000, item number 60364ES76; antioxidant 1010 comes from Youfeng Chemical; the base fabric is polyester fabric, which comes from Haoyu Textiles, a powerful supplier, item number HY2189.

[0020] Example 1

[0021] Step 1: add 1 mol of citric acid, 2 mol of polyethylene glycol, and 0.05 mol of p-toluenesulfonic acid to 2 mol of toluene, heat to 130°C and reflux, react for 20 hours, and distill under reduced pressure; add 3 mol of anhydrous ethanol and 2.4 mol of thionyl chloride, reflux at 70°C, react for 10 hours, dehydrate, add 2 mol of aminopropyltriethoxysilane, reflux at 90°C, react for 6 hours, cool, wash, and dry to obtain a modified cross-linking agent;

[0022] Step 2: 85 g of polyethylene glycol, 4 g of 1,4-butanediol, 2 g of a modified crosslinking agent and 0.2 g of an antioxidant 1010 were mixed, heated and stirred at 110°C to mix evenly, vacuum dried and dehydrated for 2.5 h, cooled to 65°C, 35 g of isophorone diisocyanate and 0.1 g of stannous octoate were added, reacted for 20 min, discharged, sealed and packaged, and placed in a 70°C oven for aging for 6 h to obtain a polyurethane hot melt adhesive;

[0023] Step 3: Take the base fabric and scour it at 100°C and a bath ratio of 25:1 for 30 minutes; after washing with clean water for 15 minutes, take out the base fabric, and after pre-setting treatment, melt the polyurethane hot melt adhesive at 190°C and apply it on the surface of the base fabric, and the coating thickness is 0.01mm; obtain a breathable adhesive lining fabric for coated fabrics; wherein the pre-setting treatment method is that the base fabric passes through 9 setting chambers in sequence, and the temperatures of each setting chamber are: 100°C for chamber one, 110°C for chamber two, 120°C for chamber three, 140°C for chamber four, 145°C for chamber five, 150°C for chamber six, 155°C for chamber seven, 160°C for chamber eight, and 170°C for chamber nine, and the vehicle speed is 30m / min.

[0024] Example 2

[0025] Step 1: add 1 mol of citric acid, 2 mol of polyethylene glycol, and 0.05 mol of p-toluenesulfonic acid to 2 mol of toluene, heat to 135°C and reflux, react for 22 hours, and distill under reduced pressure; add 3 mol of anhydrous ethanol and 2.4 mol of thionyl chloride, reflux at 75°C, react for 10 hours, dehydrate, add 2 mol of aminopropyltriethoxysilane, reflux at 95°C, react for 6 hours, cool, wash, and dry to obtain a modified cross-linking agent;

[0026] Step 2: 85 g of polyethylene glycol, 4 g of 1,4-butanediol, 2 g of a modified crosslinking agent and 0.2 g of an antioxidant 1010 were mixed, heated and stirred at 115°C to mix evenly, vacuum dried and dehydrated for 2.5 h, cooled to 65°C, 35 g of isophorone diisocyanate and 0.1 g of stannous octoate were added, reacted for 20 min, discharged, sealed and packaged, and placed in a 70°C oven for aging for 7 h to obtain a polyurethane hot melt adhesive;

[0027] Step 3: Take the base fabric and scour it at 100°C and a bath ratio of 28:1 for 30 minutes; after washing with clean water for 15 minutes, take out the base fabric, and after pre-setting treatment, melt the polyurethane hot melt adhesive at 190°C and apply it on the surface of the base fabric, and the coating thickness is 0.01mm; obtain a breathable adhesive lining fabric for coated fabrics; wherein the pre-setting treatment method is that the base fabric passes through 9 setting chambers in sequence, and the temperatures of each setting chamber are: 100°C for chamber one, 110°C for chamber two, 120°C for chamber three, 140°C for chamber four, 145°C for chamber five, 150°C for chamber six, 155°C for chamber seven, 160°C for chamber eight, and 170°C for chamber nine, and the vehicle speed is 30m / min.

[0028] Example 3

[0029] Step 1: Add 1 mol of citric acid, 2 mol of polyethylene glycol, and 0.05 mol of p-toluenesulfonic acid to 2 mol of toluene, heat to 140°C and reflux, react for 26 hours, and distill under reduced pressure; add 3 mol of anhydrous ethanol and 2.4 mol of thionyl chloride, reflux at 80°C, react for 15 hours, dehydrate, add 2 mol of aminopropyltriethoxysilane, reflux at 100°C, react for 6 hours, cool, wash, and dry to obtain a modified cross-linking agent;

[0030] Step 2: 85 g of polyethylene glycol, 4 g of 1,4-butanediol, 2 g of a modified crosslinking agent and 0.2 g of an antioxidant 1010 were mixed, heated at 130° C. and stirred to mix evenly, vacuum dried and dehydrated for 2.5 h, cooled to 75° C., 35 g of isophorone diisocyanate and 0.1 g of stannous octoate were added, reacted for 30 min, discharged, sealed and packaged, and placed in a 70° C. oven for aging for 8 h to obtain a polyurethane hot melt adhesive;

[0031] Step 3: Take the base fabric and scour it at 100°C and a bath ratio of 26:1 for 30 minutes; after washing with clean water for 15 minutes, take out the base fabric, and after pre-setting treatment, melt the polyurethane hot melt adhesive at 190°C and apply it on the surface of the base fabric, and the coating thickness is 0.01mm; obtain a breathable adhesive lining fabric for coated fabrics; wherein the pre-setting treatment method is that the base fabric passes through 9 setting chambers in sequence, and the temperatures of each setting chamber are: 100°C for chamber one, 110°C for chamber two, 120°C for chamber three, 140°C for chamber four, 145°C for chamber five, 150°C for chamber six, 155°C for chamber seven, 160°C for chamber eight, and 170°C for chamber nine, and the vehicle speed is 30m / min.

[0032] Example 4

[0033] Step 1: add 1 mol of citric acid, 2 mol of polyethylene glycol, and 0.05 mol of p-toluenesulfonic acid to 2 mol of toluene, heat to 135°C and reflux, react for 26 hours, and distill under reduced pressure; add 3 mol of anhydrous ethanol and 2.4 mol of thionyl chloride, reflux at 80°C, react for 12 hours, dehydrate, add 2 mol of aminopropyltriethoxysilane, reflux at 95°C, react for 8 hours, cool, wash, and dry to obtain a modified cross-linking agent;

[0034] Step 2: 85 g of polyethylene glycol, 4 g of 1,4-butanediol, 2 g of a modified crosslinking agent and 0.2 g of an antioxidant 1010 were mixed, heated and stirred at 115°C to mix evenly, vacuum dried and dehydrated for 2.5 h, cooled to 70°C, 35 g of isophorone diisocyanate and 0.1 g of stannous octoate were added, reacted for 22 min, discharged, sealed and packaged, and placed in a 75°C oven for aging for 6.5 h to obtain a polyurethane hot melt adhesive;

[0035] Step 3: Take the base fabric and scour it at 100°C and a bath ratio of 27:1 for 30 minutes; after washing with clean water for 15 minutes, take out the base fabric, and after pre-setting treatment, melt the polyurethane hot melt adhesive at 190°C and apply it on the surface of the base fabric, and the coating thickness is 0.01mm; obtain a breathable adhesive lining fabric for coated fabrics; wherein the pre-setting treatment method is that the base fabric passes through 9 setting chambers in sequence, and the temperatures of each setting chamber are: 100°C for chamber one, 110°C for chamber two, 120°C for chamber three, 140°C for chamber four, 145°C for chamber five, 150°C for chamber six, 155°C for chamber seven, 160°C for chamber eight, and 170°C for chamber nine, and the vehicle speed is 30m / min.

[0036] Example 5

[0037] Step 1: add 1 mol of citric acid, 2 mol of polyethylene glycol, and 0.05 mol of p-toluenesulfonic acid to 2 mol of toluene, heat to 130°C and reflux, react for 21 hours, and distill under reduced pressure; add 3 mol of anhydrous ethanol and 2.4 mol of thionyl chloride, reflux at 75°C, react for 11 hours, dehydrate, add 2 mol of aminopropyltriethoxysilane, reflux at 95°C, react for 7 hours, cool, wash, and dry to obtain a modified crosslinking agent;

[0038] Step 2: 85 g of polyethylene glycol, 4 g of 1,4-butanediol, 2 g of a modified crosslinking agent and 0.2 g of an antioxidant 1010 were mixed, heated and stirred at 135° C. to mix evenly, vacuum dried and dehydrated for 2.5 h, cooled to 75° C., 35 g of isophorone diisocyanate and 0.1 g of stannous octoate were added, reacted for 22 min, discharged, sealed and packaged, and placed in an oven at 85° C. for aging for 7.5 h to obtain a polyurethane hot melt adhesive;

[0039] Step 3: Take the base fabric and scour it at 100°C and a bath ratio of 29:1 for 30 minutes; after washing with clean water for 15 minutes, take out the base fabric, and after pre-setting treatment, melt the polyurethane hot melt adhesive at 190°C and apply it on the surface of the base fabric, and the coating thickness is 0.01mm; obtain a breathable adhesive lining fabric for coated fabrics; wherein the pre-setting treatment method is that the base fabric passes through 9 setting chambers in sequence, and the temperatures of each setting chamber are: 100°C for chamber one, 110°C for chamber two, 120°C for chamber three, 140°C for chamber four, 145°C for chamber five, 150°C for chamber six, 155°C for chamber seven, 160°C for chamber eight, and 170°C for chamber nine, and the vehicle speed is 30m / min.

[0040] Example 6

[0041] Step 1: Add 1 mol of citric acid, 2 mol of polyethylene glycol, and 0.05 mol of p-toluenesulfonic acid to 2 mol of toluene, heat to 140°C and reflux, react for 26 hours, and distill under reduced pressure; add 3 mol of anhydrous ethanol and 2.4 mol of thionyl chloride, reflux at 80°C, react for 15 hours, dehydrate, add 2 mol of aminopropyltriethoxysilane, reflux at 100°C, react for 8 hours, cool, wash, and dry to obtain a modified cross-linking agent;

[0042] Step 2: 85 g of polyethylene glycol, 4 g of 1,4-butanediol, 2 g of a modified crosslinking agent and 0.2 g of an antioxidant 1010 were mixed, heated and stirred at 140° C. to mix evenly, vacuum dried and dehydrated for 2.5 h, cooled to 75° C., 35 g of isophorone diisocyanate and 0.1 g of stannous octoate were added, reacted for 30 min, discharged, sealed and packaged, and placed in a 90° C. oven for aging for 8 h to obtain a polyurethane hot melt adhesive;

[0043] Step 3: Take the base fabric and scour it at 100°C and a bath ratio of 30:1 for 30 minutes; after washing with clean water for 15 minutes, take out the base fabric, and after pre-setting treatment, melt the polyurethane hot melt adhesive at 190°C and apply it on the surface of the base fabric, and the coating thickness is 0.01mm; obtain a breathable adhesive lining fabric for coated fabrics; wherein the pre-setting treatment method is that the base fabric passes through 9 setting chambers in sequence, and the temperatures of each setting chamber are: 100°C for chamber one, 110°C for chamber two, 120°C for chamber three, 140°C for chamber four, 145°C for chamber five, 150°C for chamber six, 155°C for chamber seven, 160°C for chamber eight, and 170°C for chamber nine, and the vehicle speed is 30m / min.

[0044] Comparative Example 1

[0045] The polyurethane hot melt adhesive was prepared without adding a modified crosslinking agent, and the other parameters were the same as those in Example 1.

[0046] Step 1: 85 g of polyethylene glycol, 4 g of 1,4-butanediol and 0.2 g of antioxidant 1010 were mixed, heated at 110° C. and stirred to mix evenly, vacuum dried and dehydrated for 2.5 h, cooled to 65° C., 35 g of isophorone diisocyanate and 0.1 g of stannous octoate were added, reacted for 20 min, discharged, sealed and packaged, and placed in a 70° C. oven for aging for 6 h to obtain a polyurethane hot melt adhesive;

[0047] Step 2: Take the base fabric and scour it at 100°C and a bath ratio of 25:1 for 30 minutes; after washing with clean water for 15 minutes, take out the base fabric, and after pre-setting treatment, melt the polyurethane hot melt adhesive at 190°C and apply it on the surface of the base fabric, and the coating thickness is 0.01mm; obtain a breathable adhesive lining fabric for coated fabrics; wherein the pre-setting treatment method is that the base fabric passes through 9 setting chambers in sequence, and the temperatures of each setting chamber are: 100°C for chamber one, 110°C for chamber two, 120°C for chamber three, 140°C for chamber four, 145°C for chamber five, 150°C for chamber six, 155°C for chamber seven, 160°C for chamber eight, and 170°C for chamber nine, and the vehicle speed is 30m / min.

[0048] Comparative Example 2

[0049] Aminopropyl triethoxysilane was directly added to prepare a modified polyurethane hot melt adhesive, and the other parameters were the same as those in Example 2.

[0050] Step 1: 85 g of polyethylene glycol, 4 g of 1,4-butanediol, 2 g of aminopropyl triethoxysilane and 0.2 g of antioxidant 1010 were mixed, heated at 115 ° C and stirred to mix evenly, vacuum dried and dehydrated for 2.5 h, cooled to 65 ° C, 35 g of isophorone diisocyanate and 0.1 g of stannous octoate were added, reacted for 20 min, discharged, sealed and packaged, and placed in a 70 ° C oven for aging for 7 h to obtain a polyurethane hot melt adhesive;

[0051] Step 2: Take the base fabric and scour it at 100°C and a bath ratio of 28:1 for 30 minutes; after washing with clean water for 15 minutes, take out the base fabric, and after pre-setting treatment, melt the polyurethane hot melt adhesive at 190°C and apply it on the surface of the base fabric, and the coating thickness is 0.01mm; obtain a breathable adhesive lining fabric for coated fabrics; wherein the pre-setting treatment method is that the base fabric passes through 9 setting chambers in sequence, and the temperatures of each setting chamber are: 100°C for chamber one, 110°C for chamber two, 120°C for chamber three, 140°C for chamber four, 145°C for chamber five, 150°C for chamber six, 155°C for chamber seven, 160°C for chamber eight, and 170°C for chamber nine, and the vehicle speed is 30m / min.

[0052] Comparative Example 3

[0053] The order of preparing the modified cross-linking agent by polyethylene glycol and aminopropyltriethoxysilane was changed, and the other parameters were the same as those in Example 3.

[0054] Step 1: 1 mol of citric acid, 3 mol of anhydrous ethanol and 2.4 mol of thionyl chloride are refluxed at 80° C. for 15 hours, 2 mol of aminopropyltriethoxysilane is added after dehydration, refluxed at 100° C. for 6 hours, 2 mol of polyethylene glycol and 0.05 mol of p-toluenesulfonic acid are added to 2 mol of toluene, the temperature is raised to 140° C. for reflux, the reaction is performed for 26 hours, and vacuum distillation is performed; cooling, washing and drying are performed to obtain a modified crosslinking agent;

[0055] Step 2: 85 g of polyethylene glycol, 4 g of 1,4-butanediol, 2 g of a modified crosslinking agent and 0.2 g of an antioxidant 1010 were mixed, heated at 130° C. and stirred to mix evenly, vacuum dried and dehydrated for 2.5 h, cooled to 75° C., 35 g of isophorone diisocyanate and 0.1 g of stannous octoate were added, reacted for 30 min, discharged, sealed and packaged, and placed in a 70° C. oven for aging for 8 h to obtain a polyurethane hot melt adhesive;

[0056] Step 3: Take the base fabric and scour it at 100°C and a bath ratio of 26:1 for 30 minutes; after washing with clean water for 15 minutes, take out the base fabric, and after pre-setting treatment, melt the polyurethane hot melt adhesive at 190°C and apply it on the surface of the base fabric, and the coating thickness is 0.01mm; obtain a breathable adhesive lining fabric for coated fabrics; wherein the pre-setting treatment method is that the base fabric passes through 9 setting chambers in sequence, and the temperatures of each setting chamber are: 100°C for chamber one, 110°C for chamber two, 120°C for chamber three, 140°C for chamber four, 145°C for chamber five, 150°C for chamber six, 155°C for chamber seven, 160°C for chamber eight, and 170°C for chamber nine, and the vehicle speed is 30m / min.

[0057] experiment:

[0058] The test method for the peel strength of adhesive interlining refers to FZ / T 01085-2018. The specific operation process is as follows:

[0059] Sample preparation: Cut the adhesive interlinings in Examples 1 to 6 and Comparative Examples 1 to 3 to a size of 200 mm × 70 mm; Cut a polyester fabric (from Haoyu Textiles, a powerful supplier, item number HY2189) with a size of 200 mm × 80 mm as a standard fabric, place thin tissue paper between the adhesive interlining sample and the standard fabric, press and cool to obtain a combined sample, and the effective bonding area of ​​the combined sample is 50 mm × 110 mm; 5 samples are prepared for each group of experiments, and the average value is taken as the final test result;

[0060] Initial peel strength: Use a tensile testing machine to uniformly stretch and peel at a speed of 100mm / min. When the combined fabric with an actual bonding width of 50mm is peeled off by 100mm, stop stretching and read the value; each group of experiments is tested 5 times in total, and the average value is recorded as the initial peel strength;

[0061] Water treatment peel strength: soak the combined sample in 25℃ clean water for 24h, take it out and dry it to constant weight, and test the peel strength according to the above method, which is recorded as water treatment peel strength;

[0062] Thermal treatment peel strength: The combined sample was thermally treated at 200° C. under vacuum conditions for 12 h. After cooling, the peel strength was tested according to the above method and recorded as the thermal treatment peel strength.

[0063] project Initial peel strength / N Water treatment peel strength / N Heat treatment peel strength / N Example 1 24.9 23.6 20.6 Example 2 25.1 24.8 21.2 Example 3 25.3 24.2 21.7 Example 4 25.7 24.4 21.8 Example 5 25.8 24.7 22.4 Example 6 25.4 24.1 22.0 Comparative Example 1 22.7 19.4 17.6 Comparative Example 2 20.6 / / Comparative Example 3 18.4 16.7 12.3

[0064] Conclusion: The data of Examples 1 to 6 show that the adhesive interlining prepared by the present invention has good water resistance and heat resistance. After water treatment and heat treatment, the peel strength does not change much. At the same time, the adhesive interlining prepared by the present invention has excellent air permeability and is comfortable to wear. The data of Example 1 and Comparative Example 1 show that the adhesive interlining prepared by adding a modified crosslinking agent has better performance. This is because the modified crosslinking agent contains multiple hydroxyl groups and can react with isocyanate to obtain a crosslinked polyurethane hot melt adhesive, thereby improving the water resistance of the adhesive interlining; in addition, the modified crosslinking agent contains a siloxane bond, so the thermal stability of the polyurethane hot melt adhesive is better. In Comparative Example 2, conventional technical means are used to directly add aminopropyl triethoxysilane. Since the amino group can react with the isocyanate group to form a urea group, its dispersibility in the polyurethane hot melt adhesive is better, but the initial peel strength is lower than that of Example 2, indicating that the present invention is superior to conventional technical means. In Comparative Example 3, after changing the reaction order, the excess ethanol makes the citric acid fully react and can no longer react with polyethylene glycol. The obtained product cannot produce cross-linking with polyurethane, and the compatibility with polyurethane is greatly reduced. The initial peel strength, water resistance and heat resistance of the finally obtained adhesive interlining are far inferior to those in Example 3.

[0065] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a breathable fusible interlining for coated fabrics, characterized in that: The following steps are involved: Step 1: adding citric acid, polyethylene glycol, and p-toluenesulfonic acid to toluene, reacting, and distilling under reduced pressure; adding anhydrous ethanol and thionyl chloride, reacting, and dehydrating, and then adding aminopropyltriethoxysilane, reacting, cooling, washing, and drying to obtain a modified crosslinking agent; wherein the amount of each component, by mole, is 1 part of citric acid, 1-2 parts of polyethylene glycol, 0.005-0.05 parts of p-toluenesulfonic acid, 2 parts of toluene, 3-3.5 parts of anhydrous ethanol, 2.4-3 parts of thionyl chloride, and 2-2.2 parts of aminopropyltriethoxysilane; Step 2: Mix polyethylene glycol, 1,4-butanediol, a modified crosslinking agent and an antioxidant, heat and stir to mix evenly, vacuum dry and dehydrate, cool and add isophorone diisocyanate and stannous octoate to react, and discharge; seal and package the discharged product, and place it in an oven for aging to obtain a polyurethane hot melt adhesive; Step 3: Take the base fabric, scour it and then wash it with clean water; after the pre-setting treatment, apply the polyurethane hot melt adhesive on the surface of the base fabric, and adhere to the base fabric after melting to obtain a breathable adhesive lining fabric for the coated fabric.

2. The method for preparing a breathable fusible interlining for coated fabrics according to claim 1, characterized in that: In step 1, the preparation method of the modified cross-linking agent is as follows: citric acid, polyethylene glycol, and p-toluenesulfonic acid are added to toluene, the temperature is raised to 130-140° C., refluxed, reacted for 20-26 hours, and distilled under reduced pressure; anhydrous ethanol and thionyl chloride are added, refluxed at 70-80° C., reacted for 10-15 hours, after dehydration, aminopropyltriethoxysilane is added, refluxed at 90-100° C., reacted for 6-8 hours, cooled, washed, and dried to obtain the modified cross-linking agent.

3. The method for preparing a breathable fusible interlining for coated fabrics according to claim 1, characterized in that: In step 2, the preparation method of the polyurethane hot melt adhesive is specifically as follows: polyethylene glycol, 1,4-butanediol, a modified crosslinking agent and an antioxidant are mixed, heated and stirred at 110 to 140° C. to mix evenly, vacuum dried and dehydrated for 2 to 3 hours, cooled to 65 to 75° C., isophorone diisocyanate and stannous octoate are added, and the reaction is carried out for 20 to 30 minutes before discharging the material.

4. The method for preparing a breathable fusible interlining for coated fabrics according to claim 1, characterized in that: In step 2, the aging temperature is 70-90° C. and the aging time is 6-8 hours.

5. The method for preparing a breathable fusible interlining for coated fabrics according to claim 1, characterized in that: In step 2, the amounts of the components used are, by weight, 70 to 85 parts of polyethylene glycol, 2 to 4 parts of 1,4-butanediol, 1 to 2 parts of a modified crosslinking agent, 0.1 to 0.2 parts of an antioxidant, 25 to 35 parts of isophorone diisocyanate, and 0.05 to 0.1 parts of stannous octoate.

6. The method for preparing a breathable fusible interlining for coated fabrics according to claim 1, characterized in that: In step 3, the scouring temperature is 80-100° C., the bath ratio is 25-30:1, and the scouring time is 30-60 min.

7. The method for preparing a breathable fusible interlining for coated fabrics according to claim 1, characterized in that: In step 3, the melting temperature of the polyurethane hot melt adhesive is 150-190°C.

8. The method for preparing a breathable fusible interlining for coated fabrics according to claim 1, characterized in that: In step 3, during the pre-setting treatment, the base fabric passes through 9 setting chambers in sequence, and the temperatures of each setting chamber are: 100-120°C for chamber 1, 100-120°C for chamber 2, 120-150°C for chamber 3, 120-150°C for chamber 4, 140-170°C for chamber 5, 140-170°C for chamber 6, 140-170°C for chamber 7, 140-170°C for chamber 8, and 140-170°C for chamber 9; the vehicle speed is 30-40m / min, and the door width is 120-125cm.

9. A fusible interlining fabric prepared by the method for preparing a breathable fusible interlining fabric for coated fabrics according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Polyurethane hot melt adhesive for adhesive interlinings and preparation method thereof

    CN101760164A

  • Reactive polyurethane hot melt adhesive for high-moisture-permeability functional fabric and preparation method thereof

    CN108251039A